Low-density high-thermal-strength austenitic heat-resistant cast steel and preparation method thereof

CN122979756APending Publication Date: 2026-10-27SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611392539.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有的奥氏体耐热铸钢通常以Fe、Ni、Cr为基、铸态或热处理后基体组织为奥氏体的一类耐热铸钢,例如:Cr-Ni系、Cr-Ni-Nb系、Cr-Ni-Mo系及高Cr高Ni的耐热铸钢,该类材料在900℃以下时、具有较好的服役性能(即具备优异的高温抗氧化、抗渗碳、抗热疲劳和高温强度),但针对1000℃及以上的轻质薄壁复杂铸件,该类材料存在以下问题:一、Ni含量高,材料密度大、成本高,不利于轻量化和大批量应用;二、普通Cr-Ni系耐热铸钢在1000℃长期氧化环境下、易形成不连续或疏松氧化膜,抗氧化剥落能力不足;三、现有技术通过提高耐热铸钢中Al的含量,虽然有利于形成Al2O3保护膜并降低密度,但Al过量易导致奥氏体稳定性下降,形成铁素体或脆性金属间化合物,同时易与N形成粗大AlN颗粒,降低塑性、热疲劳性能和铸造开裂抗力;同时,Nb、Ti等碳氮化物会缓慢向粗大AlN相转变,伴随晶界Laves相析出、热强性持续下降;四、现有技术中通过Mn部分替代Ni稳定奥氏体并降低成本,但Mn含量过高时容易形成MnS夹杂,并可能在高温氧化环境中形成不稳定氧化物,降低氧化膜致密性;五、薄壁件快凝导致Cr、Al等在晶界富集,局部出现铁素体化,诱发热疲劳裂纹;六、高Cr与高Mn加速600~850℃区间σ相析出,致使韧性与抗裂性能大幅衰减

Benefits of technology

本发明通过Mn-Ni-N-Co-Cu形成稳定的基体体系:Mn、Ni、N为核心奥氏体稳定组元,通过Mn部分替代Ni实现降本减重,同时N通过间隙固溶强化稳定奥氏体、弥补Ni用量降低带来的稳定性不足,三者协同实现低镍下的全奥氏体基体;Co扩大奥氏体相区、提高奥氏体层错能,降低位错攀移与晶界滑移速率,辅助提升高温蠕变抗力,同时Co与N的交互作用有利于提升Al贫化区的N溶解度阈值,从热力学上抑制氧化膜下基体的N过饱和析出、消除界面孔隙层诱因;Cu作为弱奥氏体形成元素,辅助稳定奥氏体基体,同时在中温析出纳米ε-Cu相产生弥散强化、补充高温强度。通过Cr-Al-Y构建多层复合氧化膜:Cr优先形成外层Cr2O3膜,从而降低氧向内扩散速率、为内层Al2O3形成创造低氧环境;Al形成内层致密Al2O3保护膜,从而实现1000℃及以上长期抗氧化、同时降低合金密度实现轻质化;Y偏聚于氧化膜/基体界面,钉扎氧化膜晶粒,抑制氧化膜向内生长与空洞形成,提升氧化膜附着力与抗热震剥落能力;此外,Y与S的结合亲和力高、促使Mn在低氧环境下高效变质MnS,生成细小圆整的Y2O2S-MnS复合夹杂,降低薄壁铸件热裂敏感性,且Ca与氧的亲和力强,能够与钢中残余自由氧、Al2O3夹杂反应生成低熔点钙铝酸盐(如12CaO7Al2O3,熔点约1450℃),该类夹杂在钢液中呈液态且易上浮去除,从而进一步净化钢液、降低夹杂物总量,避免后续稀土生成高熔点硬夹杂,为稀土硫化物变质创造低氧环境。通过Nb-Ti-Zr组成的组织调控体系:Nb、Ti优先与C、N 结合形成细小弥散颗粒,钉扎晶界、提高热强性,同时消耗自由N,初步抑制粗大AlN生成;ZrN热力学稳定性高于AlN,从根源上阻断Nb/Ti碳氮化物向AlN 的长期时效转变,同时ZrN与AlN晶格错配度低、能够作为AlN的异质形核基底,使得服役过程中析出的AlN全部呈纳米级弥散生长,将原本粗大AlN转化为补充强化相,实现“有害相无害化+强化相补充”的双重增益。通过B-Mg组成的缺陷调控体系:B尺寸小、易扩散至氧化膜/基体界面,与过饱和N结合生成纳米六方BN颗粒,进一步消耗过剩N,避免连续气孔层形成,且BN可缓解热应力失配;同时,B偏聚于奥氏体晶界,能够降低晶界能、阻碍Cr原子向晶界扩散,抑制中温σ相的形核与长大;此外,还能够强化晶界结合力,提升高温塑韧性与热疲劳性能。Mg与钢中溶解O、Al反应生成尖晶石质点,与δ-Fe晶格错配度小,能够作为凝固过程的异质形核核心,细化一次枝晶间距,大幅减轻Cr、Al的枝晶偏析,避免晶界局部铁素体化;同时 尖晶石质点能够作为Nb、Ti、Zr碳氮化物的形核基底,进一步提升析出强化效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979756A_ABST
    Figure CN122979756A_ABST
Patent Text Reader

Abstract

The application provides a low-density high-thermal-strength austenitic heat-resistant cast steel, and relates to the field of heat-resistant cast steel.The heat-resistant cast steel comprises C, Si, Mn, Cr, Ni, Al, N, Nb, Ti, Mo, Zr, B, Co, Mg, Ca, Cu, Y, P≤0.03%, S≤0.015%, and the balance of Fe and inevitable impurities.The heat-resistant cast steel can keep a stable austenitic matrix, good oxidation resistance, high thermal strength and excellent casting performance under the premise of light weight and low density, and simultaneously solves the problems of strengthening phase conversion and performance attenuation of the austenitic heat-resistant cast steel under long-term aging, and improves the thermal shock spalling resistance at 1000 DEG C and above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heat-resistant cast steel technology, and in particular to a low-density, high-heat-strength austenitic heat-resistant cast steel and its preparation method. Background Technology

[0002] Austenitic heat-resistant cast steel is widely used in heat treatment furnace components, burner parts, guide vanes, exhaust systems, industrial furnace rollers, support frames, and other high-temperature service castings due to its excellent high-temperature structural stability, oxidation resistance, thermal fatigue resistance, and casting formability.

[0003] Existing austenitic heat-resistant cast steels are typically Fe, Ni, and Cr-based, with an austenitic matrix structure in the as-cast or heat-treated state. Examples include Cr-Ni, Cr-Ni-Nb, Cr-Ni-Mo, and high-Cr, high-Ni heat-resistant cast steels. These materials exhibit good service performance below 900℃ (i.e., excellent high-temperature oxidation resistance, carburization resistance, thermal fatigue resistance, and high-temperature strength). However, for lightweight, thin-walled, complex castings operating at 1000℃ and above, these materials present the following problems: 1. High Ni content leads to high material density and cost, hindering lightweighting and mass production; 2. Ordinary Cr-Ni heat-resistant cast steels are prone to forming discontinuous or loose oxide films under long-term oxidizing conditions at 1000℃, resulting in insufficient resistance to oxidation and spalling; 3. Existing technologies, while increasing the Al content in heat-resistant cast steel to improve the formation of... While Al forms an Al2O3 protective film and reduces density, excessive Al content can lead to decreased austenite stability, forming ferrite or brittle intermetallic compounds. It also readily combines with N to form coarse AlN particles, reducing plasticity, thermal fatigue performance, and resistance to casting cracking. Simultaneously, carbonitrides such as Nb and Ti slowly transform into coarse AlN phases, accompanied by Laves phase precipitation at grain boundaries and a continuous decrease in thermal strength. Fourth, existing technologies use Mn to partially replace Ni to stabilize austenite and reduce costs, but excessive Mn content easily forms MnS inclusions and may form unstable oxides in high-temperature oxidizing environments, reducing the density of the oxide film. Fifth, rapid solidification of thin-walled parts leads to the enrichment of Cr and Al at grain boundaries, resulting in localized ferritization and inducing thermal fatigue cracks. Sixth, high Cr and high Mn content accelerate the precipitation of σ phase in the 600–850℃ range, causing a significant decrease in toughness and crack resistance. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention aims to provide a low-density, high-thermal-strength austenitic heat-resistant cast steel. This heat-resistant cast steel can maintain a stable austenitic matrix, good oxidation resistance, high thermal strength, and excellent casting performance while being lightweight and low-density. At the same time, it solves the problems of strengthening phase transformation and performance degradation under long-term aging of austenitic heat-resistant cast steel, improves its thermal shock resistance to spalling at 1000℃ and above, reduces the hot cracking sensitivity of thin-walled castings, and broadens the service temperature range of the material.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned low-density, high-heat-strength austenitic heat-resistant cast steel.

[0006] The objective of this invention is achieved through the following technical solution: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by weight percentage: C: 0.08%–0.22%, Si: 0.6%–1.8%, Mn: 4%–9%, ​​Cr: 20%–26%, Ni: 6%–12%, Al: 1%–4%, N: 0.05%–0.18%, Nb: 0.05%–0.3%, Ti: 0.02%–0.15%, Mo… 0-1.2%, Zr: 0.005%-0.03%, B: 0.002%-0.008%, Co: 0.1%-0.4%, Mg: 0.001%-0.005%, Ca: 0.003%-0.01%, Cu: 0.2%-0.6%, Y: 0.008%-0.025%, P≤0.03%, S≤0.015%, balance being Fe and unavoidable impurities.

[0007] Based on further optimization of the above scheme, the composition of the heat-resistant cast steel is further optimized as follows: C: 0.12%–0.18%, Si: 0.9%–1.4%, Mn: 5.5%–7.5%, Cr: 22%–24.5%, Ni: 7.5%–10%, Al: 1.8%–3%, N: 0.08%–0.14%, Nb: 0.1%–0.22%, Ti: 0.04%–0.1%, Mn ... o: 0.3%~0.8%, Zr: 0.01%~0.02%, B: 0.003%~0.006%, Co: 0.2%~0.3%, Mg: 0.002%~0.004%, Ca: 0.005%~0.008%, Cu: 0.3%~0.5%, Y: 0.012%~0.02%, P≤0.02%, S≤0.01%, balance Fe and unavoidable impurities.

[0008] Based on further optimization of the above scheme, the mass ratio of Al to N in the heat-resistant cast steel is 18 to 22:1.

[0009] A method for preparing low-density, high-heat-strength austenitic heat-resistant cast steel, comprising: Step S1, Ingredient Preparation: Weigh the raw materials according to the designed composition: scrap steel, low-carbon ferrochrome, electrolytic manganese, ferromanganese nitride, electrolytic nickel, aluminum ingots, ferroniobium, ferrotitanium, ferromolybdenum, ferrizirconium, ferroboron, ferrosilicon, metallic cobalt, electrolytic copper, silicon-calcium cored wire, pure magnesium cored wire, and yttrium ferrosilicon alloy (yttrium-based heavy rare earth ferrosilicon alloy); all raw materials should be derusted and degreased, and rare earth and easily oxidized raw materials should be sealed and stored. Step S2, Smelting: Add scrap steel, low-carbon ferrochrome, electrolytic nickel, electrolytic manganese, ferromolybdenum, metallic cobalt, and electrolytic copper to an induction furnace (such as a medium-frequency induction furnace or a vacuum induction furnace) for smelting; after smelting, take samples to analyze the basic composition, and adjust C, Si, Mn, Cr, Ni, Mo, Co, and Cu to the target range to obtain molten steel; Step S3, Pre-deoxidation and Al alloying: Cool the molten steel and add ferrosilicon for pre-deoxidation; after pre-deoxidation, add aluminum ingots, then take acid-soluble aluminum samples and control the acid-soluble aluminum content within the target range; Step S4, Calcium Treatment: Cool the molten steel and feed it into a silicon-calcium cored wire; Step S5, Multi-element alloying: Cool the molten steel and add ferroniobium, ferromanganese nitride, ferrotitanium, ferrizirconium, and ferroboron in sequence, stirring to dissolve; Step S6, Magnesium Refining Treatment: Cool the molten steel and feed in pure magnesium cored wire; Step S7, Yttrium-based composite modification: Before tapping, the silicon-yttrium-iron alloy is pressed into the lower part of the molten steel using a pressing method, and then tapped after stirring; Step S8, Pouring: Pour the molten steel after tapping into the casting shell / sand mold to obtain a heat-resistant casting; Step S9, Heat Treatment: After cleaning the casting, perform solution treatment and stabilization treatment.

[0010] Based on further optimization of the above scheme, in step S1, degreasing and rust removal specifically includes: For scrap steel: Place the scrap steel in a bogie kiln / incinerator with ventilation gaps between layers, heat it to 300-400℃ and hold it for 1-2 hours (using high temperature to vaporize and pyrolyze the oil), then let it cool naturally to below 100℃ before removing it from the furnace. Clean the surface of any residual carbon black with compressed air. If it is also rusty, incinerate it and then proceed to the shot blasting process to remove the rust. For blocky ferroalloys such as low-carbon ferrochrome, ferromanganese nitride, ferroniobium, ferrotitanium, ferromolybdenum, ferrizirconium, ferroboron, ferrosilicon, and ferrosilicon yttrium, the surface is first wiped 2-3 times with a lint-free cloth and industrial anhydrous ethanol, allowed to evaporate naturally, and then shot blasting is performed. The shot blasting process is as follows: the raw material is evenly laid out (avoiding stacking and obstruction, ensuring that the shot can cover all surfaces), the shot blasting line speed is 60-80 m / s, the treatment time is 5-15 min, and after shot blasting, compressed air at 0.4-0.6 MPa is used to blow away residual steel shot and dust on the surface until the surface has a uniform metallic luster and no flaky oxide scale or loose rust is removed. For pure metal materials such as electrolytic manganese, electrolytic nickel, metallic cobalt, and electrolytic copper, first wipe the surface 2-3 times with a lint-free cloth and industrial anhydrous ethanol, let it evaporate and dry naturally, then use an angle grinder with a steel wire wheel and a stainless steel wire brush to grind until the metal substrate is exposed, and blow away the dust. For aluminum ingots, wipe the surface oil stains directly with a dry lint-free cloth or with anhydrous industrial ethanol. For cored wires such as silicon-calcium cored wire and pure magnesium cored wire, remove the outer plastic film, wipe the surface oil stains with a dry cloth and alcohol, seal and store after wiping, and remove as needed.

[0011] Based on further optimization of the above scheme, in the process of degreasing and derusting, the raw materials treated by wet method need to be kept at 200-300℃ for 2-4 hours to achieve drying.

[0012] Based on further optimization of the above scheme, in step S2, the temperature is first increased from room temperature to 590-610℃ at a heating rate of 5-8℃ / min and held for 30-60min (to remove moisture absorbed by the furnace charge and lining, and prevent material collapse), then increased to 1190-1210℃ at a heating rate of 10-15℃ / min and held for 10-20min (to gradually soften and collapse the furnace charge), and then increased to 1590-1650℃ at a heating rate of 8-12℃ / min and held for 15-25min; after that... After holding at 1590–1650℃ for 10–15 minutes, turn on the electromagnetic stirrer at 60%–70% of the rated power (corresponding to a stirring current of 95–105A) and stir for 5–8 minutes. After stirring, let it stand for 2–3 minutes, take samples to analyze the basic components C, Si, Mn, Cr, Ni, Mo, Co, Cu and residual N, and add the corresponding raw materials to adjust to the target range. After adding, hold at 1600–1620℃ for 5–8 minutes and stir twice to obtain molten steel.

[0013] Based on further optimization of the above scheme, in step S3, the molten steel is cooled to 1560-1600℃, and ferrosilicon is pressed below the surface of the molten steel. Electromagnetic stirring is turned on at 30%-40% of the rated power (corresponding to a stirring current of 65-70A) for 1-2 minutes to complete pre-deoxidation. Then, aluminum ingots are evenly divided into 2-3 batches and pressed into the bottom of the molten steel. After all the aluminum ingots are added, the temperature is maintained for 2-3 minutes, and electromagnetic stirring is performed at 30%-40% of the rated power for 1 minute. After that, an acid-soluble aluminum sample is taken, and the acid-soluble aluminum content is controlled within the target range.

[0014] Based on further optimization of the above scheme, in step S4, the molten steel is cooled to 1550-1570℃, and silicon-calcium cored wire is fed in at a uniform speed of 10-15m / min using a wire feeder. After the wire feeding is completed, electromagnetic stirring is performed for 2-3 minutes at 30%-40% of the rated power (to promote the floating of low-melting-point calcium aluminate inclusions). Then, the free oxygen in the molten steel is detected by a constant oxygen probe (to ensure that the free oxygen is ≤20ppm; if it does not meet the standard, a small amount of silicon-calcium cored wire is added).

[0015] Based on further optimization of the above scheme, in step S5, the molten steel is cooled to 1540-1560℃, and ferroniobium, ferromanganese nitride, ferrotitanium, ferrizirconium, and ferroboron are added in sequence. After each alloy is added, the mixture is electromagnetically stirred for 1 minute at 30%-40% of the rated power. After all alloys are added, the mixture is kept at the temperature for 3-5 minutes. Samples are taken to analyze the contents of N, Nb, Ti, Zr, and B, and the corresponding raw materials are added according to the analysis results to adjust the mixture to the target range.

[0016] Based on further optimization of the above scheme, in step S6, the molten steel is cooled to 1520-1540℃, and pure magnesium cored wire is fed in at a uniform speed of 15-25m / min using a wire feeder. Argon gas is introduced during the wire feeding process to protect the liquid surface (reduce magnesium vapor oxidation and burn-off). After the wire feeding is completed, electromagnetic stirring is performed at 30%-40% of the rated power for 2-3 minutes (to promote the uniform dispersion of MgAl2O4 particles and the floating of large particles).

[0017] Based on further optimization of the above scheme, in step S7, 1 to 2 minutes before tapping, the silicon-yttrium-iron alloy is pressed into the lower part of the molten steel using the pressing method. After being added, the steel is electromagnetically stirred for 30 to 60 seconds at 30% to 40% of the rated power, and then tapped immediately (to reduce the high-temperature burn-off of rare earth elements).

[0018] Based on further optimization of the above scheme, in step S8, after the molten steel is tapped into the ladle, it is calmed for 3-5 minutes (to allow large inclusions to float fully, and at the same time adjust the temperature to the target pouring value); before the molten steel is tapped, the casting shell / sand mold is preheated, heated from room temperature to 290-310℃ at 5-8℃ / min and held for 0.9-1.1h, then heated to 500-550℃ at 3-5℃ / min and held for 2-4h (to ensure uniform temperature inside and outside the shell); after calming, the molten steel is filled into the mold at an initial rate of 100-150mm / s, and after filling the pouring cup, the speed is increased to 150-250mm / s, and the speed is reduced when the cavity is almost filled (to avoid splashing and slag entrapment), and the steel flow is kept continuous and stable throughout the process, and interruption of flow is prohibited.

[0019] Based on further optimization of the above scheme, in step S9, the solution treatment is specifically as follows: the furnace loading temperature is ≤300℃ (to avoid thermal stress cracking of thin-walled castings), the temperature is raised to 1080~1150℃ at a heating rate of 8~10℃ / min, and held for 1~4h; forced air cooling after exiting the furnace: wind speed 3~5m / s, cooling rate ≥100℃ / min (to quickly pass through the carbide precipitation zone and obtain supersaturated uniform austenite).

[0020] Based on further optimization of the above scheme, in step S9, the stabilization treatment is specifically as follows: after the solution treatment is cooled to room temperature, it is loaded into the furnace and heated to 800-900℃ at a heating rate of 10-12℃ / min, held at the temperature for 2-8 hours, and then cooled to room temperature with air after being removed from the furnace, thus obtaining the solution.

[0021] The following are the technical effects of this solution: This invention establishes a stable matrix system using Mn-Ni-N-Co-Cu: Mn, Ni, and N are the core austenite stabilizing components. Mn partially replaces Ni to reduce costs and weight, while N strengthens and stabilizes austenite through interstitial solid solution, compensating for the stability deficiency caused by the reduced Ni content. The three components work synergistically to achieve a fully austenitic matrix under low nickel content. Co expands the austenite phase region, increases the austenite stacking fault energy, reduces dislocation climb and grain boundary slip rates, and helps improve high-temperature creep resistance. At the same time, the interaction between Co and N helps to increase the N solubility threshold in the Al-depleted region, thermodynamically inhibiting N supersaturation precipitation in the matrix under the oxide film and eliminating the cause of interfacial pore layers. Cu, as a weak austenite forming element, helps stabilize the austenitic matrix and simultaneously precipitates nano-ε-Cu phase at intermediate temperatures to produce dispersion strengthening and supplement high-temperature strength. A multi-layer composite oxide film is constructed using Cr-Al-Y: Cr preferentially forms an outer Cr2O3 film, thereby reducing the rate of oxygen diffusion inward and creating a low-oxygen environment for the formation of the inner Al2O3 layer; Al forms a dense inner Al2O3 protective film, achieving long-term oxidation resistance at 1000℃ and above, while simultaneously reducing alloy density for lightweighting; Y segregates at the oxide film / substrate interface, pinning oxide film grains, inhibiting inward growth and void formation, and improving oxide film adhesion and thermal shock resistance; furthermore, Y has a high affinity for S, promoting efficient transformation of Mn into MnS in a low-oxygen environment, generating fine and rounded Y2O2S-MnS composite inclusions, reducing the hot cracking sensitivity of thin-walled castings, and Ca has a strong affinity for oxygen, reacting with residual free oxygen and Al2O3 inclusions in steel to form low-melting-point calcium aluminates (such as 12CaO). 7Al2O3 (melting point approximately 1450℃) is a liquid inclusion in molten steel that is easily floated and removed, thus further purifying the steel, reducing the total amount of inclusions, preventing the subsequent formation of high-melting-point hard inclusions from rare earth elements, and creating a low-oxygen environment for rare earth sulfide degradation. Through a microstructure control system composed of Nb-Ti-Zr: Nb and Ti preferentially combine with C and N to form fine, dispersed particles, pinning grain boundaries and improving thermal strength, while simultaneously consuming free N, initially inhibiting the formation of coarse AlN; ZrN has higher thermodynamic stability than AlN, fundamentally blocking the long-term aging transformation of Nb / Ti carbonitrides into AlN. Furthermore, ZrN has a low lattice mismatch with AlN and can serve as a heterogeneous nucleation substrate for AlN, ensuring that all AlN precipitated during service grows in a nanoscale dispersed manner, transforming the originally coarse AlN into a supplementary strengthening phase, achieving a dual benefit of "harmful phase neutralization + strengthening phase supplementation". The defect control system composed of B-Mg utilizes the following characteristics: B, with its small size, easily diffuses to the oxide film / matrix interface, combining with supersaturated N to form nano-hexagonal BN particles, further consuming excess N and preventing the formation of continuous porous layers. BN can also alleviate thermal stress mismatch. Simultaneously, B segregates at austenite grain boundaries, reducing grain boundary energy, hindering Cr atom diffusion to grain boundaries, and suppressing the nucleation and growth of the mid-temperature σ phase. Furthermore, it strengthens grain boundary bonding, improving high-temperature ductility, toughness, and thermal fatigue performance. Mg reacts with dissolved O and Al in steel to form spinel particles, which have a small lattice mismatch with δ-Fe, serving as heterogeneous nucleation nuclei during solidification, refining primary dendrite spacing, significantly reducing Cr and Al dendrite segregation, and preventing localized ferritification at grain boundaries. Simultaneously, spinel particles can serve as a nucleation substrate for Nb, Ti, and Zr carbonitrides, further enhancing precipitation strengthening effects.

[0022] The heat-resistant cast steel prepared by this invention significantly improves long-term service stability, thermal shock resistance to spalling, casting yield and toughness, and medium-temperature catalytic resistance, thereby avoiding problems such as strengthening attenuation after long-term service, large-area spalling after thermal shock cycles, and high defect rate of thin-walled gradual thermal cracking, while ensuring the basic advantages of heat-resistant cast steel being lightweight and low-cost. Attached Figure Description

[0023] Figure 1 This is a flowchart illustrating the preparation process of heat-resistant cast steel in an embodiment of the present invention.

[0024] Figure 2 This is a physical image of the heat-resistant cast steel used in an embodiment of the present invention. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.

[0026] Example 1: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.12%, Si: 0.9%, Mn: 5.5%, Cr: 22%, Ni: 7.5%, Al: 1.8%, N: 0.09%, Nb: 0.1%, Ti: 0.04%, Mo: 0.3%, Zr: 0.01%, B: 0.003%, Co: 0.2%, Mg: 0.002%, Ca: 0.005%, Cu: 0.3%, Y: 0.012%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0027] Example 2: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Co: 0.25%, Mg: 0.003%, Ca: 0.006%, Cu: 0.45%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0028] Example 3: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.18%, Si: 1.4%, Mn: 7.5%, Cr: 24.5%, Ni: 10%, Al: 3%, N: 0.14%, Nb: 0.22%, Ti: 0.1%, Mo: 0.8%, Zr: 0.02%, B: 0.006%, Co: 0.3%, Mg: 0.004%, Ca: 0.008%, Cu: 0.5%, Y: 0.02%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0029] Example 4: A method for preparing low-density, high-heat-strength austenitic heat-resistant cast steel, used to prepare any of the heat-resistant cast steels in Examples 1 to 3, comprising: Step S1, Ingredient Preparation: Weigh the raw materials according to the designed composition: scrap steel, low-carbon ferrochrome, electrolytic manganese, ferromanganese nitride, electrolytic nickel, aluminum ingots, ferroniobium, ferrotitanium, ferromolybdenum, ferrizirconium, ferroboron, ferrosilicon, metallic cobalt, electrolytic copper, silicon-calcium cored wire, pure magnesium cored wire, and yttrium ferrosilicon alloy (yttrium-based heavy rare earth ferrosilicon alloy); all raw materials should be derusted and degreased, and rare earth and easily oxidized raw materials should be sealed and stored. The specific steps for degreasing and rust removal are: For scrap steel: Place the scrap steel in a bogie kiln / incinerator with ventilation gaps between layers, heat it to 300-400℃ and hold it for 1-2 hours (preferably 350℃ for 1.5 hours, using high temperature to vaporize and pyrolyze the oil). Then let it cool naturally to below 100℃ before removing it from the furnace. Clean the surface of any residual carbon black with compressed air. If it is also rusty, incinerate it and then proceed to the shot blasting process to remove the rust. For blocky ferroalloys such as low-carbon ferrochrome, ferromanganese nitride, ferroniobium, ferrotitanium, ferromolybdenum, ferrizirconium, ferroboron, ferrosilicon, and ferrosilicon yttrium, the surface is first wiped 2-3 times (preferably 2 times) with a lint-free cloth and industrial anhydrous ethanol, and then allowed to air dry naturally. Shot blasting is then performed. Specifically, the raw material is evenly laid out (avoiding stacking and ensuring the shot covers all surfaces), the shot blasting speed is 60-80 m / s (preferably 70 m / s), and the treatment time is 5-15 minutes (preferably 10 minutes). After shot blasting, compressed air at 0.4-0.6 MPa (preferably 0.5 MPa) is used to blow away residual steel shot and dust until the surface exhibits a uniform metallic luster, with no flaky oxide scale or loose rust. For pure metal materials such as electrolytic manganese, electrolytic nickel, metallic cobalt, and electrolytic copper, first wipe the surface 2-3 times (preferably 2 times) with a lint-free cloth and industrial anhydrous ethanol, let it evaporate and dry naturally, then use an angle grinder with a steel wire wheel and a stainless steel wire brush to grind until the metal substrate is exposed, and blow away the dust. For aluminum ingots, wipe the surface oil stains directly with a dry lint-free cloth or with anhydrous industrial ethanol. For cored wires such as silicon-calcium cored wire and pure magnesium cored wire, remove the outer plastic film, wipe the surface oil stains with a dry cloth and alcohol, seal and store after wiping, and remove as needed.

[0030] During the degreasing and derusting process, the raw materials treated by wet method need to be kept at 200-300℃ (preferably 250℃) for 2-4 hours (preferably 3 hours) to achieve drying.

[0031] Step S2, Smelting: Scrap steel, low-carbon ferrochrome, electrolytic nickel, electrolytic manganese, ferromolybdenum, metallic cobalt, and electrolytic copper are added to an induction furnace (such as a medium-frequency induction furnace or a vacuum induction furnace) for smelting. First, the temperature is raised from room temperature to 590–610°C (preferably 600°C) at a heating rate of 5–8°C / min (preferably 6.5°C / min), held for 30–60 min (preferably 45 min, to remove excess material and absorb moisture from the furnace lining and prevent material collapse). Then, the temperature is raised to 1190–1210°C (preferably 1200°C) at a heating rate of 10–15°C / min (preferably 12.5°C / min), held for 10–20 min (preferably 15 min, to gradually remove excess material from the furnace lining). First, soften the sludge, then heat it to 1590-1650℃ (preferably 1620℃) at a heating rate of 8-12℃ / min (preferably 10℃ / min) and hold it for 15-25min (preferably 20min); then, hold it at 1590-1650℃ (preferably 1620℃) for 10-15min (preferably 12.5min), then turn on the electromagnetic stirrer at 60%-70% of the rated power (corresponding to a stirring current of 95-105A) (preferably 65%, corresponding to a stirring current of 100A), stir for 5-8min (preferably 6.5min), and let it stand for 2-3min (preferably 2.5min) after stirring. After smelting, samples are taken for analysis of the basic components C, Si, Mn, Cr, Ni, Mo, Co, Cu and residual N, and corresponding raw materials are added to adjust to the target range. After adding, the mixture is held at 1600-1620℃ (preferably 1610℃) for 5-8 minutes (preferably 6.5 minutes) while being stirred twice to obtain molten steel.

[0032] Step S3, Pre-deoxidation and Al alloying: Cool the molten steel to 1560-1600℃ (preferably 1580℃), and press the ferrosilicon below the surface of the molten steel. Turn on the electromagnetic stirrer at 30%-40% of the rated power (corresponding to a stirring current of 65-75A) (preferably 35%, corresponding to a stirring current of 70A), and stir for 1-2 minutes (preferably 1.5 minutes) to complete the pre-deoxidation. Then, divide the aluminum ingots evenly into 2-3 batches (preferably 2 batches) and press them into the bottom of the molten steel. After all the aluminum ingots are added, keep them at the temperature for 2-3 minutes (preferably 2.5 minutes), and then electromagnetically stir for 1 minute at 30%-40% (preferably 35%) of the rated power. After that, take an acid-soluble aluminum sample and control the acid-soluble aluminum content within the target range.

[0033] Step S4, Calcium Treatment: Cool the molten steel to 1550-1570℃ (preferably 1560℃), and feed the silicon-calcium cored wire at a uniform speed of 10-15m / min (preferably 12.5 m / min) using a wire feeder. After feeding, perform electromagnetic stirring for 2-3 minutes (preferably 2.5 minutes, to promote the floating of low-melting-point calcium aluminate inclusions) at 30%-40% (preferably 35%) of the rated power. Then, use a constant oxygen probe to detect the free oxygen in the molten steel (ensure that the free oxygen is ≤20ppm; if it does not meet the standard, feed a small amount of silicon-calcium cored wire).

[0034] Step S5, Multi-element alloying: Cool the molten steel to 1540-1560℃ (preferably 1550℃), and add ferroniobium, ferromanganese nitride, ferrotitanium, ferrizirconium, and ferroboron in sequence. After each alloy is added, electromagnetically stir for 1 minute at 30%-40% (preferably 35%) of the rated power. After all alloys are added, hold at the temperature for 3-5 minutes (preferably 4 minutes). Take samples to analyze the contents of N, Nb, Ti, Zr, and B, and add the corresponding raw materials according to the analysis results to adjust to the target range.

[0035] Step S6, Magnesium Refining Treatment: Cool the molten steel to 1520-1540℃ (preferably 1530℃), and feed pure magnesium cored wire at a uniform speed of 15-25m / min (preferably 20m / min) using a wire feeder. During the wire feeding process, argon gas is introduced to protect the liquid surface (to reduce magnesium vapor oxidation and burn-off). After the wire feeding is completed, electromagnetic stirring is performed at 30%-40% (preferably 35%) of the rated power for 2-3 minutes (preferably 2.5 minutes, to promote uniform dispersion of MgAl2O4 particles and the floating of large particles).

[0036] Step S7, Yttrium-based composite modification: 1-2 minutes (preferably 1.5 minutes) before tapping, the silicon-yttrium-iron alloy is pressed into the lower part of the molten steel using the pressing method. After adding, the steel is electromagnetically stirred for 30-60 seconds (preferably 45 seconds) at 30%-40% (preferably 35%) of the rated power, and then tapped immediately (to reduce the high-temperature burn-off of rare earth elements).

[0037] Step S8, Pouring: After the molten steel is poured into the ladle, it is allowed to settle for 3-5 minutes (preferably 4 minutes, to allow large inclusions to float to the surface and simultaneously adjust the temperature to the target pouring value). Before pouring, the casting shell / sand mold is preheated by raising the temperature from room temperature to 290-310℃ (preferably 300℃) at a rate of 5-8℃ / min (preferably 6.5℃ / min), holding it at that temperature for 0.9-1.1 hours (preferably 1 hour), and then raising the temperature again at a rate of 3-5℃ / min (preferably 4℃ / min) to... The temperature is 500-550℃ (preferably 525℃), and the temperature is maintained for 2-4 hours (preferably 3 hours to ensure uniform temperature inside and outside the mold). After being killed, the molten steel is filled into the mold at an initial rate of 100-150 mm / s (preferably 125 mm / s). After filling the pouring cup, the speed is increased to 150-250 mm / s (preferably 200 mm / s). When the mold cavity is almost filled, the speed is reduced (gradually reducing the filling rate until the pouring is slow to avoid splashing and slag entrapment). The steel flow is kept continuous and stable throughout the process, and interruption of flow is prohibited.

[0038] Step S9, Heat Treatment: After cleaning the casting, perform solution treatment and stabilization treatment; The solution treatment is as follows: the furnace loading temperature is ≤300℃ (to avoid thermal stress cracking of thin-walled castings), the temperature is raised to 1080~1150℃ (preferably 1115℃) at a heating rate of 8~10℃ / min (preferably 9℃ / min), and held for 1~4h (1~2h when the wall thickness is ≤6mm, and 3~4h when it is greater than 6mm); forced air cooling after exiting the furnace: wind speed 3~5m / s (preferably 4m / s), cooling rate ≥100℃ / min (to quickly pass through the carbide precipitation zone and obtain supersaturated uniform austenite).

[0039] The stabilization treatment is as follows: after solution treatment and cooling to room temperature, the solution is loaded into a furnace and heated to 800-900℃ (preferably 850℃) at a heating rate of 10-12℃ / min (preferably 11℃ / min). The temperature is held for 2-8 hours (2-4 hours for wall thickness ≤6mm, 6-8 hours for wall thickness >6mm). This allows Nb, Ti, and Zr carbonitrides to disperse and precipitate, pinning grain boundaries and improving high-temperature creep strength. Although this temperature range is partially within the σ phase precipitation sensitive range (i.e., 600-850℃), the segregation of B at grain boundaries can effectively suppress σ phase nucleation. Furthermore, Nb, Ti, and Zr preferentially combine with C and N to precipitate, consuming Cr and Mo elements near the grain boundaries, further reducing the driving force for σ phase precipitation. The solution is then removed from the furnace and cooled to room temperature with air to obtain the final product.

[0040] Comparative Example 1: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, B: 0.004%, Co: 0.25%, Mg: 0.003%, Ca: 0.006%, Cu: 0.45%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0041] Comparative Example 2: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, Co: 0.25%, Mg: 0.003%, Ca: 0.006%, Cu: 0.45%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0042] Comparative Example 3: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Mg: 0.003%, Ca: 0.006%, Cu: 0.45%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0043] Comparative Example 4: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Co: 0.25%, Ca: 0.006%, Cu: 0.45%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0044] Comparative Example 5: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Co: 0.25%, Mg: 0.003%, Cu: 0.45%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0045] Comparative Example 6: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Co: 0.25%, Mg: 0.003%, Ca: 0.006%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0046] Comparative Example 7: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Co: 0.25%, Mg: 0.003%, Ca: 0.006%, Cu: 0.45%, Y: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0047] Comparative Example 8: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Co: 0.25%, Mg: 0.003%, Ca: 0.006%, Cu: 0.45%, Ce: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0048] Comparative Example 9: A low-density, high-heat-strength austenitic heat-resistant cast steel comprises the following components by mass percentage: C: 0.15%, Si: 1.15%, Mn: 6.5%, Cr: 23.2%, Ni: 8.7%, Al: 2.4%, N: 0.12%, Nb: 0.16%, Ti: 0.07%, Mo: 0.55%, Zr: 0.015%, B: 0.004%, Co: 0.25%, Mg: 0.003%, Ca: 0.006%, Cu: 0.45%, La: 0.016%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

[0049] The room temperature tensile strength and room temperature elongation after fracture of the heat-resistant cast steels in Examples 1-3 and Comparative Examples 1-9 were tested according to the relevant standards of GB / T 228.1-2021 "Metallic Materials - Tensile Testing - Part 1: Room Temperature Test Method". The tensile strength of the heat-resistant cast steels in Examples 1-3 and Comparative Examples 1-9 at 1000℃ was tested according to the relevant standards of GB / T 228.2-2015 "Metallic Materials - Tensile Testing - Part 2: High Temperature Test Method". The high temperature strength retention rate after 1000℃ and 100h was also tested according to the relevant standards of GB / T 228.2-2015 "Metallic Materials - Tensile Testing - Part 2: High Temperature Test Method". The high temperature strength retention rate was calculated as (tensile strength at 1000℃ after 100h aging / tensile strength at 1000℃ without aging) × 100%. The relevant standards of GB / T 13303-1991 "Method for Determination of Oxidation Resistance of Steel" were used to test the weight gain of heat-resistant cast steels in Examples 1-3 and Comparative Examples 1-9 after oxidation at 1000℃ for 100 hours. The oxidation weight gain was calculated as (mass after oxidation - initial mass) / total surface area of ​​the sample. The relevant standards of GB / T 38231-2019 "Corrosion of Metals and Alloys - Thermal Cycling Oxidation Test Method for Metallic Materials under High-Temperature Corrosion Conditions" were used to test the number of large-area peelings of the oxide film in Examples 1-3 and Comparative Examples 1-9 after water-cooling thermal shock at 1000℃ (a peeled oxide film area ≥ 5% of the total surface area was considered "large-area peeling"). The test results are shown in the table below.

[0050] As shown in the table above, the embodiments of the present invention achieve a synergistic breakthrough in "low density, low cost, high thermal strength, and high oxidation resistance" of heat-resistant cast steel through the synergistic control of "austenite stabilization + oxide film construction + microstructure regulation + defect suppression". This breaks the mutual constraint relationship between strength, plasticity, oxidation resistance, and thermal shock resistance (currently, room temperature tensile strength > 620 MPa, elongation > 28%, 1000℃ tensile strength > 110 MPa, and oxidation weight gain < 0.5 mg / cm²). At the same time, this alloy system has a high tolerance for compositional deviations and good stability for industrial mass production.

Claims

1. A low-density, high-heat-strength austenitic heat-resistant cast steel, characterized in that: The heat-resistant cast steel comprises the following components by mass percentage: C: 0.08%–0.22%, Si: 0.6%–1.8%, Mn: 4%–9%, ​​Cr: 20%–26%, Ni: 6%–12%, Al: 1%–4%, N: 0.05%–0.18%, Nb: 0.05%–0.3%, Ti: 0.02%–0.15%, Mo: 0–1.2%, Zr: 0.005%–0.03%, B: 0.002%–0.008%, Co: 0.1%–0.4%, Mg: 0.001%–0.005%, Ca: 0.003%–0.01%, Cu: 0.2%–0.6%, Y: 0.008%–0.025%, P≤0.03%, S≤0.015%, with the balance being Fe and unavoidable impurities.

2. The low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 1, characterized in that: The composition of the heat-resistant cast steel is further optimized as follows: C: 0.12%–0.18%, Si: 0.9%–1.4%, Mn: 5.5%–7.5%, Cr: 22%–24.5%, Ni: 7.5%–10%, Al: 1.8%–3%, N: 0.08%–0.14%, Nb: 0.1%–0.22%, Ti: 0.04%–0.1%, Mo: 0.3%–0.8%, Zr: 0.01%–0.02%, B: 0.003%–0.006%, Co: 0.2%–0.3%, Mg: 0.002%–0.004%, Ca: 0.005%–0.008%, Cu: 0.3%–0.5%, Y: 0.012%–0.02%, P≤0.02%, S≤0.01%, with the balance being Fe and unavoidable impurities.

3. The method for preparing a low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 1 or 2, characterized in that: include: Step S1, Ingredient Preparation: Weigh the raw materials according to the designed composition: scrap steel, low-carbon ferrochrome, electrolytic manganese, ferromanganese nitride, electrolytic nickel, aluminum ingots, ferroniobium, ferrotitanium, ferromolybdenum, ferrizirconium, ferroboron, ferrosilicon, metallic cobalt, electrolytic copper, silicon-calcium cored wire, pure magnesium cored wire, and yttrium-iron silicon alloy; all raw materials are derusted and degreased, and rare earth and easily oxidized raw materials are sealed and stored. Step S2, Smelting: Scrap steel, low-carbon ferrochrome, electrolytic nickel, electrolytic manganese, ferromolybdenum, metallic cobalt, and electrolytic copper are added to an induction furnace for smelting; after smelting, samples are taken for analysis of the basic composition, and C, Si, Mn, Cr, Ni, Mo, Co, and Cu are adjusted to the target range to obtain molten steel; Step S3, Pre-deoxidation and Al alloying: Cool the molten steel and add ferrosilicon for pre-deoxidation; after pre-deoxidation, add aluminum ingots, then take acid-soluble aluminum samples and control the acid-soluble aluminum content within the target range; Step S4, Calcium Treatment: Cool the molten steel and feed it into a silicon-calcium cored wire; Step S5, Multi-element alloying: Cool the molten steel and add ferroniobium, ferromanganese nitride, ferrotitanium, ferrizirconium, and ferroboron in sequence, stirring to dissolve; Step S6, Magnesium Refining Treatment: Cool the molten steel and feed in pure magnesium cored wire; Step S7, Yttrium-based composite modification: Before tapping, the silicon-yttrium-iron alloy is pressed into the lower part of the molten steel using a pressing method, and then tapped after stirring; Step S8, Pouring: Pour the molten steel after tapping into the casting shell / sand mold to obtain a heat-resistant casting; Step S9, Heat Treatment: After cleaning the casting, perform solution treatment and stabilization treatment.

4. The preparation method of a low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 2 or 3, characterized in that: In step S1, the degreasing and rust removal specifically includes: For scrap steel: Place the scrap steel in a bogie kiln / incinerator with ventilation gaps between layers, heat it to 300-400℃, hold it for 1-2 hours, and then let it cool naturally to below 100℃ before taking it out of the furnace. Clean the residual carbon black on the surface with compressed air. If it is also rusty, incinerate it and then proceed to the shot blasting process to remove the rust. For blocky ferroalloys such as low-carbon ferrochrome, ferromanganese nitride, ferroniobium, ferrotitanium, ferromolybdenum, ferrizirconium, ferroboron, ferrosilicon, and yttrium silicon alloy, the surface is first wiped 2-3 times with a lint-free cloth and industrial anhydrous ethanol, allowed to evaporate naturally and then shot blasting is performed. The shot blasting process is as follows: the raw material is evenly laid out, the shot blasting linear speed is 60-80 m / s, the treatment time is 5-15 min, and after shot blasting, it is blown with compressed air at 0.4-0.6 MPa. For pure metal materials such as electrolytic manganese, electrolytic nickel, metallic cobalt, and electrolytic copper, first wipe the surface 2-3 times with a lint-free cloth and industrial anhydrous ethanol, let it evaporate and dry naturally, then use an angle grinder with a steel wire wheel and a stainless steel wire brush to grind until the metal substrate is exposed, and blow away the dust. For aluminum ingots, wipe the surface oil stains directly with a dry lint-free cloth or with anhydrous industrial ethanol. For cored wires such as silicon-calcium cored wire and pure magnesium cored wire, remove the outer plastic film, wipe the surface oil stains with a dry cloth and alcohol, seal and store after wiping, and remove as needed.

5. The preparation method of a low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 4, characterized in that: During the degreasing and rust removal process, the raw materials treated by wet method need to be kept at 200-300℃ for 2-4 hours to achieve drying.

6. The preparation method of a low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 5, characterized in that: In step S2, the temperature is first increased from room temperature to 590–610°C at a rate of 5–8°C / min and held for 30–60 min. Then, the temperature is increased to 1190–1210°C at a rate of 10–15°C / min and held for 10–20 min. After that, the temperature is increased to 1590–1650°C at a rate of 8–12°C / min and held for 15–25 min. Then, the temperature is held at 1590–1650°C for 10–15 min, and then an electromagnetic stirrer is turned on at 60%–70% of the rated power for 5–8 min. After stirring, the mixture is allowed to stand for 2–3 min. Samples are taken to analyze the basic components C, Si, Mn, Cr, Ni, Mo, Co, Cu and residual N. Corresponding raw materials are added to adjust the temperature to the target range. After adding the raw materials, the temperature is held at 1600–1620°C for 5–8 min while stirring twice to obtain molten steel.

7. The preparation method of a low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 6, characterized in that: In step S3, the molten steel is cooled to 1560-1600℃, and ferrosilicon is pressed below the surface of the molten steel. The electromagnetic stirring is turned on at 30%-40% of the rated power and stirred for 1-2 minutes to complete the pre-deoxidation. Then, aluminum ingots are evenly divided into 2-3 batches and pressed into the bottom of the molten steel. After all the aluminum ingots are added, the temperature is maintained for 2-3 minutes, and electromagnetic stirring is performed at 30%-40% of the rated power for 1 minute. Then, an acid-soluble aluminum sample is taken, and the acid-soluble aluminum content is controlled within the target range.

8. The preparation method of a low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 7, characterized in that: In step S4, the molten steel is cooled to 1550-1570℃, and silicon-calcium cored wire is fed into it at a uniform speed of 10-15m / min using a wire feeder. After the wire feeding is completed, electromagnetic stirring is performed at 30%-40% of the rated power for 2-3 minutes, and then the free oxygen in the molten steel is detected by a constant oxygen probe.

9. The preparation method of a low-density, high-heat-strength austenitic heat-resistant cast steel according to claim 8, characterized in that: In step S5, the molten steel is cooled to 1540–1560°C, and ferroniobium, ferromanganese nitride, ferrotitanium, ferrizirconium, and ferroboron are added in sequence. After each alloy is added, the mixture is electromagnetically stirred for 1 minute at 30%–40% of its rated power. After all alloys are added, the mixture is kept at this temperature for 3–5 minutes. Samples are taken to analyze the contents of N, Nb, Ti, Zr, and B, and the corresponding raw materials are added according to the analysis results to adjust the mixture to the target range.